Negotiating Religious Identity in State Schools Within the Flow of National Curriculum Policy - Tita Pertamawati; Bernardus Agus Rukiyanto; Edina Asifarani (Mahkota Science Publishers, 2025)
Religious identity in Indonesian public schools is not a stand-alone entity, but rather part of a broader social construct of Indonesianness and modernity. The purpose of this study is to explore in depth how religious identity is negotiated in Indonesian public schools amid the dynamics of an ever-changing national curriculum policy. This study uses library research by combining relevant inter-theoretical interactions. The results confirm that the negotiation of religious identity in Indonesian public schools is not merely a clash between state secularism and expressions of faith, but a manifestation of the nation's efforts to rewrite the relationship between religion, morality, and nationality. Public schools become a space for cultural politics where teachers and students transform policy into meaningful practice, making the curriculum both an ideological text and an arena for ethical dialogue. In this process, religiosity does not oppose secularism, but rather reinterprets it into a spiritual awareness that respects diversity. Thus, national education finds its most profound meaning not merely in producing obedient citizens but in making people who are reflectively faithful, critically rational, and authentically pluralistic.